A comparison of simple side-channel analysis countermeasures for variable-base elliptic curve scalar multiplication - Nascimento, Erick; Abarzúa, Rodrigo; López, Julio; Dahab, Ricardo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2014)
Side-channel attacks are a growing threat to implementations of cryptographic systems. This article examines the state of the art of algorithmic countermeasures against simple side-channel attacks on elliptic curve cryptosystems defined over prime fields. We evaluate the security versus computation cost trade-offs of SSCA countermeasures for variable-base scalar multiplication algorithms without precomputation. The expected performance impact of each countermeasure is analyzed regarding their computational cost in terms of finite field operations.